Successful management of severe red blood cell alloimmunization in pregnancy with a combination of therapeutic plasma exchange, intravenous immune globulin, and intrauterine transfusion. Issue 3 (17th December 2017) - Nwogu, Laura C.; Moise, Kenneth J.; Klein, Kimberly L.; Tint, Hlaing; Castillo, Brian; Bai, Yu
Abstract : BACKGROUND: Antibodies to Rhesus and Kell antigens have been associated with severe hemolytic disease of the fetus and newborn (HDFN) necessitating intrauterine transfusion (IUT) of red blood cells (RBCs). We report a case series of five women with severe HDFN secondary to maternal RBC alloimmunization who were successfully managed with therapeutic plasma exchange (TPE), intravenous immune globulin (IVIG), and IUT. STUDY DESIGN AND METHODS: This is a retrospective case series of five women with severe HDFN who underwent a total of three TPE procedures during Weeks 10 to 13 of pregnancy, followed by weekly IVIG infusions. They were followed with serial middle cerebral artery peak systolic velocity studies beginning at 16 weeks' gestation to detect fetal anemia. For IUT, fetuses were administered RBC units that fully matched the maternal phenotype to D, C, E, K, Fy, Jk, and S antigen groups. The delivery outcomes and newborn information were followed. RESULTS: Anti‐D and anti‐K alloantibodies were implicated in HDFN. A two‐ to fourfold dilution reduction in anti‐D and anti‐K titers was observed after TPE. IUT was initiated between 21 to 27 weeks' gestation. The total number of IUTs for each patient ranged from four to seven. All five women delivered healthy infants at 33 to 38 weeks' gestation. CONCLUSION: A combined regimen of TPE and IVIG early in pregnancy and IUT later in pregnancy results in successful management of severe maternal RBC alloimmunization and HDFN. IUT with fully phenotypically matched RBC units may help prevent further RBC alloimmunization in complex cases of HDFN.